UPAYA PENINGKATAN MINAT BELAJAR PENDIDIKAN KEWARGANEGARAAN MELALUI MODEL PEMBELAJARAN (PKn) STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) - Maryanto Maryanto (Khazanah Pendidikan, 2009)
More than 60% of students in SMP Negeri 2 Pulosari were not interested in following Civic lesson. This action research is aimed at improving the student’s interest in following the civic lesson. The research was done in two cycles each of which consisted of planning, acting, observing, and reflection. Data was collected through observation, questionnaire, and test. Based on the data analysis it could be concluded that STAD (student team achievement division) was effective in improving students’ activeness; the average of which being 63.33% in cycle 1 and 80% in cycle 2. Key words: improving, interest, Civic, STAD.